Bubbling Cauldron : Race, Ethnicity, and the Urban Crisis. - Smith, Michael Peter (University of Minnesota Press, 1995)
How can race and ethnicity be understood as questions of power? How do changes among racial and ethnic groups alter conflicts about these groups identities and the resultant power structure shaped by these conflicts? The contributors to this important new volume take up these questions and others as they delve beneath the turbulent surface of racial and ethnic relations in urban centers worldwide.